Towards relieving center segregation in twin-roll cast Al-Mg-Si-Cu strips by controlling the thermal-mechanical process. (10th June 2023) - Zhang, Shao-You; Wang, Xuan; Mo, Yuan-Ting; Wang, Cheng; Cheng, Tuo; Ivasishin, Orest; Ma, Pin-Kui; Wang, Hui-Yuan
Highlights: The twin-roll cast 6061 strip with alleviative center segregation was achieved. The mitigation of center segregation was related to the thermal-mechanical process. The change of cooling rate could affect the phase selection of Fe-containing phase. The α-AlFeSi shows favorable crystallographic matching with Mg2 Si and Q phases. Three matching planes between α-AlFeSi and Q/Mg2 Si were examined by EBSD analysis. Abstract: Serious center segregation greatly limits the application of twin-roll casting (TRC) technology for producing 6xxx alloy strips. Herein, Al-0.9Mg-0.6Si-0.2Cu-0.1Fe (wt.%, 6061) strips with different thicknesses were fabricated by TRC, and we found that the center segregation was well relieved with the thickness increased from 3 mm to 4 mm. To reveal the mechanisms of mitigation of center segregation in the 4 mm strip, various techniques including solidification simulation, crystallographic calculation, electron backscatter diffraction (EBSD), and electron probe micro-analyzer (EPMA) were utilized. The results disclosed that the Fe-containing phase in the 3 mm strip was π-AlFeMgSi, while the counterpart in the 4 mm strip was α-AlFeSi. The α-AlFeSi could serve as nucleation substrates for Mg2 Si and Q-AlCuMgSi phases, thus promoting the uniform distribution of elements and preventing the accumulation of phases in the center region. Three matching planes between the α-AlFeSi and Q/Mg2 Si were examined as: (11 2 ¯ 0)α-AlFeSi // (0001)Q, (0001)α-AlFeSi // (110)Mg2Si, and (11 2 ¯ 0)α-AlFeSi // (1 1 ¯ 0)Mg2Si . Meanwhile, the smaller roll separating force during the TRC process in the 4 mm strip could weaken the force-induced liquid flow behavior in the semi-solid region, which is the other reason for the alleviation of center segregation. Owing to the elimination of the center segregation, a more excellent fracture elongation was achieved in the as-homogenized 4 mm strip (∼29%) compared with the counterpart of the 3 mm strip (∼20%). This work may provide a strategy to eliminate the center segregation, thus further promoting the application of TRC process and producing high-performance Al alloy strips efficiently. Graphical abstract: Image, graphical abstract